Suicídio, sobrevivente e aconselhamento pastoral: reflexões no vale da sombra da morte - Pena, Giani Mota Brandão (2012)
Despite its current high incidence, the ecclesiastical environment still lacks forums for discussions and projects on the suicide issue. Thus, this work aims at dealing with this subject in this environment and, in particular, with the implications that influence the practice of Pastoral Counseling. Therefore, biblical accounts closely related to suicide were looked into, as well as the social and psychological aspects of this phenomenon in society, through statistics. To support this research, an opinion poll was carried out in the ecclesiastical community of Brasilia, DF, whereby its members suicide perceptions could be analyzed, as well as their expectations concerning the role of the church when dealing with that issue. In order to humanize the community and pastoral practices, some behavior patterns were identified and taken as instances of sensitive and careful performances towards the survivors experience of mourning. Both the descriptive analysis of the opinion poll results and the vast bibliography used could attest the great challenge to tackle the suicide issue, not only in the practice of pastoral counseling but also towards the needy survivor.